2020
DOI: 10.1111/sms.13849
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the second ventilatory threshold through ventricular repolarization profile analysis

Abstract: Under the hypothesis that sympathetic control of ventricular repolarization may change once the second ventilatory threshold (VT2) has been reached, a novel methodology for non-invasive VT2 estimation based on the analysis of the T wave from the electrocardiogram (ECG) is proposed, and potential underlying physiological mechanisms are suggested. 25 volunteers (33.4 ± 5.2 years) underwent an incremental power cycle ergometer test (25 W/minute). During the test, respiratory gas How to cite this article: Milagro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
(58 reference statements)
5
9
0
Order By: Relevance
“…It is thus valid and reproducible in both athletes who are only able to perform exercise until lower maximal workloads and in athletes capable to continue exercise tests up to very high maximum workloads. This determination of AT is similar to results previously published by Milagro et al who also found changes in the profile of ventricular repolarization instability as well as of oscillations in the low frequency spectrum once reaching the anaerobic threshold [ 21 ]. It is noteworthy that these changes in repolarization instability cannot be provoked by increased heart rate or by fixed atrial pacing [ 11 , 15 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is thus valid and reproducible in both athletes who are only able to perform exercise until lower maximal workloads and in athletes capable to continue exercise tests up to very high maximum workloads. This determination of AT is similar to results previously published by Milagro et al who also found changes in the profile of ventricular repolarization instability as well as of oscillations in the low frequency spectrum once reaching the anaerobic threshold [ 21 ]. It is noteworthy that these changes in repolarization instability cannot be provoked by increased heart rate or by fixed atrial pacing [ 11 , 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…The change in autonomic cardiac modulation during increasing workload subsequently results in altered HRV-derived parameters and this has been used to assess AT in athletes [ 24 , 25 ]. Our present study, studies assessing AT via HRV-derived parameters [ 24 , 25 ] and previous studies investigating the connection of changes in repolarization instability and AT [ 15 , 21 ] thus suggest that the autonomic control of the electrical activity of the myocardium, especially on the level of the ventricular myocardium seems to change once reaching the anaerobic threshold.…”
Section: Discussionsupporting
confidence: 73%
“…To the best of our knowledge, this study is the first one using time-frequency methods to evaluate the frequency components of dTV and RRV during rest, exercise and recovery. The results of our ECG analysis corroborate that dT oscillations are mainly contained in the LF band and their magnitude is enhanced in response to exercise-induced sympathetic stimulation [ 10 , 16 , 18 ]. These results agree well with previous reports showing enhancement of PRD, which represents the same concept as P dTV , subsequent to tilt table test and to mild exercise as well as decrease following β-adrenergic blockade [ 10 ].…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, PRD has been confirmed not to be an epiphenomenon of HR and HRV, as substantiated by the fact that fixed atrial pacing exerts modest effects on PRD despite fully abolishing HRV and despite varying HR at fixed values in a large range [ 10 , 18 ]. This has been later supported by studies using an incremental exercise test, which have described low correlation between PRD and HR or HRV [ 16 ]. Nevertheless, there is yet limited information on how PRD varies continuously with time so that a full characterization of its temporal profile following physiological sympathoexcitatory interventions can be established.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation